Pengaruh Merger Tiga Bank Syariah dan Fintech Terhadap Kepuasan Nasabah BSI KCP Muara Bungo M Yamin - Diza Ramalia; Khadijah Ath Thahirah (Yayasan Almanar Pujud, 2025)
The merger of the three main sharia banks in Indonesia into Bank Syariah Indonesia (BSI) aims to increase the competitiveness of sharia banking at the national and global level. On the other hand, developments in financial technology (fintech) are increasingly influencing consumer behavior in choosing financial services. The aim of this research is to analyze and determine the impact of the merger of three Islamic banks and integration with financial technology (fintech) on customer satisfaction at Bank Syariah Indonesia (BSI). The research method used is a quantitative approach by collecting primary data through questionnaires distributed to active BSI KCP Muara Bungo customers using the Accidental Sampling method. Data analysis was carried out using multiple linear regression with SPSS version 21. The research results show that mergers and fintech significantly influence consumer satisfaction. The merger increases operational efficiency and service quality, while fintech provides easy access and innovation in banking services. Simultaneously these two variables are able to explain variations in consumer satisfaction of 67%. This research is expected to provide useful information for bank management in improving customer service and satisfaction.